Association between dietary retinol intake and rheumatoid arthritis based on NHANES database - Yuexin Ni; Yating Cao; Yun Qiu; Yingyuan Li (BMC, 2024)
Abstract Objective This study focused on the investigation of the correlation between dietary retinol intake and rheumatoid arthritis (RA) using the National Health and Nutrition Examination Survey (NHANES) database. Methods Data from five NHANES cycles from 2003 to 2012 were utilized for this study. Dietary retinol intake was considered as the independent variable, and RA was the dependent variable. A weighted logistic regression method was applied to construct the relational model of the two variables. Stratified analysis without adjusting for confounding factors and subgroup analysis with confounding factors adjusted were conducted to explore the association between dietary retinol intake and RA. The optimal intake of dietary retinol was determined by the restricted cubic splines (RCS) analysis. Results 22,971 samples were included in this study. The weighted logistic regression model was employed to construct the relational model of dietary retinol intake and RA (OR: 0.95, 95% CI: 0.91-0.99, p = 0.019). Stratified analysis displayed a great influence on the relational model exerted by the interaction between gender and retinol intake (p for interaction = 0.014). A significant association between retinol intake and RA was also indicated in the model adjusted for demographic characteristics (OR: 0.95, 95% CI: 0.90-1.00, p = 0.029). Subgroup analysis by gender showed that in the female population, unadjusted model (OR: 0.90, 95% CI: 0.84-0.96, p = 0.002), model adjusted for demographic characteristics only (OR: 0.89, 95% CI: 0.83-0.96, p = 0.002), and model adjusted for all confounding factors (OR: 0.91, 95% CI: 0.85-0.99, p = 0.019) indicated dietary retinol intake as a protective factor against RA. RCS analysis demonstrated that in the female population, regardless of the model used (Crude, Model I, and Model II), an intake of dietary retinol > 354.86 mcg was associated with RA disease reduction (OR < 1.0, p-non-linear < 0.05, p-overall < 0.05). Conclusion Increased dietary retinol intake was associated with RA disease reduction, particularly in the female population. Women are recommended to increase their dietary retinol intake (> 354.86 mcg) to reduce the risk of RA.